Land Grant System and its Impact on the Pre-modern Central Asia - Shah, Imtiyaz (Journal of Eastern European and Central Asian Research (JEECAR), 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Pre-modern Central Asia was comprised of three principalities: 1. the Emirate of Bukhara, and Khanates of 2. Khiva and 3. Khokand. These principalities were caught in the web of socio-economic and political crises. To cope with these crises and to solve the problem of the expenditure of huge administrative costs, the Khans and Amirs distributed some portions of land from the state lands (amlok) as grants among their heirs, both civil and military officials. This paper concludes that instead of solving the problems, the distribution of land grant adversely affected the normative political order. The grantees, as landlords, began exercising enormous political and economic powers. These actions created immense exploitation of the subaltern tenants. The landlords siphoned off the tenants’ surplus and consequently subjected them to the most appalling conditions with their housing, food, and clothing.